Sanitary Quality of the Meals Served in the Canteens and Vicinity of the Lagoon Mother and Child University Hospital Centre and National Hospital and University Centre Hubert Koutoukou Maga of Cotonou (Benin) Moussiliou Paraïso, - Paraïso, Moussiliou; DEGBEY, CYRIAQUE COMLAN; Bakary Ozavino, Yasmine; Azandjemè, Colette; Sossa-Jerome, Charles (My University, 2023)
Background: Food safety is an integral part of food security. It refers to the protection of the food supply against risks of microbial, chemical and physical origin at every stage of the food chain. The study aimed to investigate the sanitary quality of meals served in the canteens and vicinity of the Lagoon Mother and Child University Hospital Centre (CHU-MEL) and National Hospital and University Centre Hubert Koutoukou Maga (CNHU-HKM) of Cotonou. Methods: It was a cross-sectional with a data collection period from 16 March to 22 April 2021. There were 32 vendors surveyed and 40 meals sampled for microbiological examination. We collected data on the vendors’ socio-demographic characteristics, working environment, health status, knowledge and food hygiene practices. Results: About 83% of the meals contained pathogenic microorganisms. All meals had a temperature from 4˚C to 60˚C called the “danger zone”. The level of knowledge about food hygiene was low in 65.7% of the vendors. About 47% had poor personal and clothing hygiene, food storage and service practices. Conclusion: These results show that the meals sold in the CHU-MEL and CNHU-HKM could present a health risk for the consumer. There is a need for improvement of the sanitary quality of the meals delivered in the canteens and vicinity of these hospitals.
Keywords: Sanitary Quality; Meals; Canteens; CHU-MEL; CNHU-HKM; Benin